The effect of solid manure dosage and cow biourine concentration on the growth and yield of shallot (Allium ascalonicum L.) Sembrani variety - Jhon Hardy Purba; Made Suarsana; Putu Sri Wahyuni; Ketut Mariasa (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
The aim of this research was to determine the effect of cow manure and cow biourine on the growth and yield of shallots. This experiment used a factorial experiment with a Randomized Group Design (RAK). The treatment tried consisted of two factors, namely the first factor was the dose of solid manure (O) with 4 levels, namely O0: without manure (control), O1: dose of 5 tons.ha-1 (0.5 kg of solid manure.petak- 1), O2: dose 10 ton.ha-1 (1.0 kg solid manure.plot-1), O3: dose 15 ton.ha-1 (1.5 kg solid manure.plot-1). The second factor is the concentration of cow biourine (U) with 4 levels, namely U0: without cow biourine (control), U1: 10% concentration or 100 ml.l-1 cow biourine, U2: 20% concentration or 200 ml.l-1 cow biourine , and U3: 30% concentration or 300 ml.l-1 bovine biourine. Each combination treatment was repeated 3 times. The treatment dose of solid cow manure had a very significant effect on the wet weight of the crown per hill and the wet weight of the tubers per hill. A dose of solid manure of 10 tons.ha-1 gave the highest wet weight of tubers per hill, namely 146.30 g. The cow biourine concentration treatment had a very significant effect on the oven dry weight of the canopy per hill, the wet weight of the canopy per hill and the number of leaves per hill at the age of 56 days after planting, 42 days after planting. A cow biourine concentration of 20% or 200 ml.l-1 gave the highest wet weight of tubers per hill, namely 127.50. The interaction between solid manure dose and cow biourine concentration had no significant effect on all observed variables.